2019
DOI: 10.2147/ceg.s214677
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficacy of the four weeks treatment of omeprazole plus mosapride combination therapy compared with that of omeprazole monotherapy in patients with proton pump inhibitor-refractory gastroesophageal reflux disease: a randomized controlled trial</p>

Abstract: Purpose The aim of this study was to compare the effect of omeprazole plus mosapride combination therapy with that of omeprazole monotherapy in proton pump inhibitor (PPI) refractory gastroesophageal reflux disease (GERD) patients. Patients and methods Patients were eligible to participate in this study if they had experienced symptoms of heartburn and/or regurgitation more than twice weekly and were unresponsive to at least 8 weeks of a standard dose of PPI. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The remaining 40 articles were subjected to full reviews, and after assessing the eligibility, we excluded a further 24 articles ( Fig. 1 ), leaving 16 articles 10 , 19 - 33 for meta-analysis ( Table 1 ). These 16 studies presented details on 1446 participants, among whom 719 were included in the PPI plus prokinetics group (mosapride, 10 , 21 , 22 , 24 , 25 , 29 - 32 , 34 domperidone, 23 , 27 , 28 revexepride, 19 , 20 and acotiamide 26 ) and 727 were included in the PPI monotherapy group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 40 articles were subjected to full reviews, and after assessing the eligibility, we excluded a further 24 articles ( Fig. 1 ), leaving 16 articles 10 , 19 - 33 for meta-analysis ( Table 1 ). These 16 studies presented details on 1446 participants, among whom 719 were included in the PPI plus prokinetics group (mosapride, 10 , 21 , 22 , 24 , 25 , 29 - 32 , 34 domperidone, 23 , 27 , 28 revexepride, 19 , 20 and acotiamide 26 ) and 727 were included in the PPI monotherapy group.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies indicated global symptom improvement of GERD in terms of a binary outcome (yes or no), 10 , 19 , 22 , 24 - 26 , 28 - 30 whereas the other 7 studies 20 , 21 , 23 , 27 , 31 - 33 reported continuous measures (ie, a change in symptom improvement). Among the 9 studies that rated global symptom improvement of GERD in terms of a binary outcome, the average percentage symptom improvement was 63.8% in the PPI plus prokinetics group, compared with 50.6% in the PPI monotherapy group.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that mosapride, a selective 5-HT 4 receptor agonist, may augment the effects of PPIs when coadministered in certain patient populations, such as those with erosive esophagitis; 73,74 however, many other studies have not been able to reproduce this significant synergistic effect with mosapride. 75,76 Rikkunshito, a traditional Japanese medicine that promotes gastric motility through the release of ghrelin, may have some effectiveness in treating refractory GERD as it also has synergistic effects on gastric motility when combined with PPIs and may be effective as monotherapy for GERD. [77][78][79][80] Further study of prokinetic agents in the setting of GERD may give light to future advances in the management of refractory GERD.…”
Section: Salivary Gland Secretionsmentioning
confidence: 99%
“…The remaining 12 studies were scrutinized, after which three more studies were rejected [ 32 , 33 , 34 ] because subjects in the control groups did not use PPIs. Finally, we included nine RCTs in our meta-analysis [ 12 , 13 , 14 , 15 , 17 , 18 , 19 , 20 , 21 ]. The details of the included RCTs are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In 2013, a systematic review concluded that mosapride combined with a PPI was not more effective than a PPI alone [ 16 ]. Since then, several RCTs have been conducted [ 17 , 18 , 19 , 20 , 21 ], and most RCTs showed that the improvement in GERD patients who received mosapride was not statistically significant, although mosapride seemed to offer a favorable result in these patients. The reason is that the sample size was not large enough to reach statistical significance.…”
Section: Introductionmentioning
confidence: 99%